2017
DOI: 10.1016/j.jacbts.2017.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Aged Human Multipotent Mesenchymal Stromal Cells Can Be Rejuvenated by Neuron-Derived Neurotrophic Factor and Improve Heart Function After Injury

Abstract: Visual Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 24 publications
2
25
0
Order By: Relevance
“…sGene, genes encoding secreted proteins; sLungGenes, genes encoding secreted proteins that are preferentially expressed in the adult lung; z-P Lung , lung-preferential expression Z score. mesenchymal stromal cells (57,58). Our analysis of the human and mouse tissue databases indicated preferential expression of Ndnf in the normal adult lung in humans (Figure 1 and Supplemental Figures 1 and 2) and mice ( Figure 1 and Supplemental Figure 3), which we validated using several approaches.…”
Section: Resultsmentioning
confidence: 57%
“…sGene, genes encoding secreted proteins; sLungGenes, genes encoding secreted proteins that are preferentially expressed in the adult lung; z-P Lung , lung-preferential expression Z score. mesenchymal stromal cells (57,58). Our analysis of the human and mouse tissue databases indicated preferential expression of Ndnf in the normal adult lung in humans (Figure 1 and Supplemental Figures 1 and 2) and mice ( Figure 1 and Supplemental Figure 3), which we validated using several approaches.…”
Section: Resultsmentioning
confidence: 57%
“…Recently, several strategies have been explored to rejuvenate senescent MSCs, and subsequently enhance their functions. Overexpression of neuron-derived neurotrophic factor was found to rejuvenate aged BM-MSCs and improve their function in repairing the aged heart after ischemia [82]. microRNA (miR)-10a rejuvenated aged BM-MSCs and enhanced the cardiacprotection following infarction in mice via increased paracrine effects [83].…”
Section: Msc Functionsmentioning
confidence: 99%
“…Recently, it was proved that young rat MSCs experienced robust tissue genesis [49] . It was confirmed that reduced regenerative capacity of aged stem cells hampers organ regeneration, but not migration due to injury [50] .…”
Section: Discussionmentioning
confidence: 84%